The contribution of free radicals in paracetamol degradation by UV/NaClO - Giang, Le Truong; Phuong, Dao Thi; Thuy, Quan Cam; Yen, Dao Hai (Vietnam Journal of Chemistry, 2017)
UV/Chlorine is an emerging advanced oxidation process which forms several reactive species including •OH, •Cl, •OCl. This study investigated the contribution of three main free radicals: •OH, •Cl, •OCl on Paracetamol degradation under different conditions. Benzoic acid (BA), Nitro benzene (NB) and DMOB were used as probe compounds. The second rate constant of •OH, •Cl, •OCl with PRC were determined: 4.19 (±0.15) ×109 M-1s-1; 3.71 1010 M-1s-1; 3.532×109 M-1s-1, respectively. The formation of free radicals depends on pH. In particular, at pH 5: the contribution of •OH and     (-•OCl, •Cl) are 45 %, 41 %, respectively, at pH 8.5, the contribution of free radicals increases up to 63 %. Keywords. Paracetamol, UV/Chlorine process, reactive species.